LightDock: a new multi-scale approach to protein-protein docking - Jiménez-García, Brian; Roel-Touris, Jorge; Romero-Durana, Miguel; Vidal, Miquel; Jiménez-González, Daniel; Fernández-Recio, Juan (Bioinformatics, 2018)
Abstract Motivation Computational prediction of protein-protein complex structure by docking can provide structural and mechanistic insights for protein interactions of biomedical interest. However, current methods struggle with difficult cases, such as those involving flexible proteins, low-affinity complexes or transient interactions. A major challenge is how to efficiently sample the structural and energetic landscape of the association at different resolution levels, given that each scoring function is often highly coupled to a specific type of search method. Thus, new methodologies capable of accommodating multi-scale conformational flexibility and scoring are strongly needed. Results We describe here a new multi-scale protein-protein docking methodology, LightDock, capable of accommodating conformational flexibility and a variety of scoring functions at different resolution levels. Implicit use of normal modes during the search and atomic/coarse-grained combined scoring functions yielded improved predictive results with respect to state-of-the-art rigid-body docking, especially in flexible cases. Availability and implementation The source code of the software and installation instructions are available for download at https://life.bsc.es/pid/lightdock/. Supplementary information Supplementary data are available at Bioinformatics online.